Web-Based Office Stationer Inventory Management Information System At BPJS Ketenagakerjaan Kudus: Sistem Informasi Pengelolaan Inventaris Alat Tulis Kantor Berbasis Web Pada BPJS Ketenagakerjaan Kudus - Seila Desy Maulia; Supriyono Supriyono (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The Kudus Branch of BPJS Ketenagakerjaan is a government agency tasked with administering the employment social security program. One crucial operational aspect is the management of office stationery (ATK) inventory to support administrative activities. The current system is still based on manual recording using notebooks and simple spreadsheets, resulting in recurring problems such as recording errors, stock data discrepancies, and slow reporting processes that hamper managerial decision-making. Previous research on web-based inventory information systems has been conducted in the context of manufacturing and financial institutions, but none has specifically accommodated the needs of a layered user hierarchy in an employment social security institution. This study develops a web-based ATK inventory management information system at BPJS Ketenagakerjaan Kudus to fill this gap. The development uses the Waterfall model with stages of needs analysis, design, implementation, testing, and maintenance. Data were collected through field observations, structured interviews, and documentation studies. The system was built using PHP (Laravel framework) and MySQL. Black box testing of eight functional modules—including login, inventory data management, incoming/outgoing transactions, real-time stock monitoring, and automated reporting—resulted in a 100% success rate with no critical errors found. The system supports a three-level access hierarchy (general users, operational staff, branch managers) that allows for inventory control according to each role. This study proves that a contextually designed web-based information system can significantly improve the efficiency and accuracy of inventory management in a government agency in the social security sector.